Length–weight relationship of six deep‐sea fish species from the shelf regions of western Bay of Bengal and Andaman waters. (30th August 2016) - Aneesh Kumar, K. V.; Thomy, R.; Deepa, K. P.; Hashim, M.; Sudhakar, M.
Summary: Length–weight relationships for six deep‐sea fish species inhabiting the shelf regions of the western Bay of Bengal and the waters of Andaman and Nicobar of India are presented. Samples were collected using high‐speed demersal trawl and expo demersal trawl nets at depths of 231–514 m in August and September 2010. The b values in the analyses ranged from 3.05 to 3.31, showing a mean and median value of 3.21 ( SE ± 0.039, SD ± 0.097) and 3.2, respectively. Comparisons of b values with earlier estimations confirm the presence of spatial and temporal variations in the length–weight relations among the species. Coefficient of determination scores ranged from 0.94 to 0.97, indicating robustness of the samples analysed. This study provides the first estimates of length–weight relationships for four of the deep‐sea fishes, enriching the understanding of the growth patterns and population dynamics of these less‐studied deep‐sea fishery resources in Indian Ocean waters.